HRM Responses to Labor Shortages and Organizational Employee Retention from a Human-centric Management Paradigm - Stor, Marzena; Haromszeki, Łukasz; Poór, József (Publishing House of Wroclaw University of Economics and Business, 2024)
["Human at the Center of the Organization: Visions, Realities, Challenges," a monograph edited by Marzena Stor, is a comprehensive exploration of the paradigm shift in organizational management that emphasizes placing humans at the core of all strategic and operational activities. The monograph delves into various critical aspects such as HRM responses to labor shortages, employee loyalty, and performance factors, and the evolution of management practices in Poland. It also addresses contemporary issues like AI-enhanced recruitment, the needs of Generation Z, and the importance of mental health and well-being in the workplace. The goal of this monograph is to provide a detailed analysis of how organizations can balance efficiency and innovation with the need to support and understand their employees. Through theoretical frameworks, empirical research findings, and practical insights, this work offers valuable strategies for enhancing employee engagement, retention, and overall organizational performance, making it an indispensable resource for HRM professionals, organizational leaders, and scholars interested in the future of human-centric management.] z zapowiedzi.
Stor, M., Haromszeki, Ł., and Poór, J. (2024). HRM Responses to Labor Shortages and Organizational Employee Retention from a Human-centric Management Paradigm. In M. Stor (Ed.), Human at the Center of the Organization: Visions, Realities, Challenges (pp. 10-25). Publishing House of Wroclaw University of Economics and Business. https://doi.org/10.15611/2024.59.8.01
Keywords: human-centric management; employee engagement; organizational performance; HRM strategies; workplace well-being